Study of the Convergence of the Laplace-Adomian Method Applied to the Telegraph Equation with Non-linearity and Source Term (European Journal of Pure and Applied Mathematics, 2026)
In this article, we study the convergence of the Laplace Adomian algorithm applied to the telegraph equation with a nonlinearity and a source term. To this end, we review some definitions and properties that enable us to establish the convergence proof, then we present a description of the method, followed by the convergence proof, and finally we propose an application of the algorithm.
Keywords: Telegraph equation, Laplace transform, Laplace-Adomian method.